2010
DOI: 10.1007/s11106-010-9225-5
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformations in Ti2Cu under destructive hydrogenation and recombination

Abstract: The thermodynamic possibility and conditions of Ti 2 Cu hydrogenation and recombination are assessed. The mechanism of Ti 2 Cu interaction with hydrogen between 293 and 973 K at pressure 1.0 MPa is studied. The interaction of Ti 2 Cu with hydrogen is thermodynamically possible in the destructive hydrogenation region over a wide temperature range. X-ray diffraction shows that destructive hydrogenation products are titanium dihydride and copper-rich intermetallic phases and copper depending on reaction condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…The lattice parameters of α phase in a Ti Cu binary system were determined to have a hexagonal structure (space group P 63/mmc) with lattice parameters of a = 0.2945 nm and c = 0.4685 nm. Also, the crystallographic characteristics of Ti 2 Cu compound are well de ned in the literature as a tetragonal structure (space group I4/mmm) with lattice parameters of a = 0.29438 nm and c = 1.0786 nm [20]. It was found that the X-ray di raction patterns of as-cast samples showed both α ′ martensite and α-Ti phases and slight peaks associated with the intermetallic Ti 2 Cu, as observed in Fig.…”
Section: Resultsmentioning
confidence: 53%
“…The lattice parameters of α phase in a Ti Cu binary system were determined to have a hexagonal structure (space group P 63/mmc) with lattice parameters of a = 0.2945 nm and c = 0.4685 nm. Also, the crystallographic characteristics of Ti 2 Cu compound are well de ned in the literature as a tetragonal structure (space group I4/mmm) with lattice parameters of a = 0.29438 nm and c = 1.0786 nm [20]. It was found that the X-ray di raction patterns of as-cast samples showed both α ′ martensite and α-Ti phases and slight peaks associated with the intermetallic Ti 2 Cu, as observed in Fig.…”
Section: Resultsmentioning
confidence: 53%
“…Regardless of the cooling rate applied, such precipitation is unavoidable. 20 Williams et al 13 reported that the supersaturated a9-martensite structure was precipitated in alloys containing up to 6 wt-%Cu during aging. The high cooling rate imposed on the samples promoted complete b phase decomposition and the formation of the acicular plates of martensite typically found in titanium alloys.…”
Section: Microstructuresmentioning
confidence: 99%
“…The microstructure of the as cast samples (in a copper mould) is in good agreement with the previously reported results. 13,14,20 In general, the fully lamellar microstructure consists of equiaxed polycrystalline grains and lamellae within the grains in the Ti alloys as show in Fig. 6.…”
Section: Microstructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously examined [7,8] the mechanism of destructive hydrogenation of Ti 3 Al and Ti 2 Cu involving the decomposition of starting intermetallides because of the selective hydrogenation of titanium in certain thermodynamic conditions. It was established that new titanium-depleted intermetallic phases formed when titanium left the starting intermetallide.…”
mentioning
confidence: 99%